ANALISIS PENGARUH PEMBIAYAAN MURABAHAH TERHADAP PROFITABILITAS UMKM PADA BSI KCP KUALA MEULABOH - ade rahmah safitri; Sari Maulida Vonna (LPPM, 2022)
This study aims to determine the effect of murabaha financing on the profitability of UMKM at BSI Kcp Kuala Meulaboh. Profitability dedicates the financial performance of an UMKM as measured by the profitability ratio. The higher the profitability ratio, the higher the picture of the profits obtained. Based on information from the Ministry of Cooperatives and UMKM, the economic crisis due to the COVID-19 pandemic has an impact on the survival of micro, small and medium enterprises. This impact forced many workers to be laid off temporarily. This study uses quantitative descriptive data. Sources of data used in this study is primary data. Data analysis in this study includes descriptive analysis and multiple regression analysis, as well as hypothesis testing using a partial significance test (t-test) with a statistical certainty level of 95% (α = 0.05). The results of this study can be concluded that there are three types of businesses that owned by respondents, namely the type of business service, trade and plantation, the number of respondents 75 murabahah financing customers has a significant positive effect on the profitability of UMKM at BSI Kcp Kuala.